2009
DOI: 10.1038/nn.2394
|View full text |Cite
|
Sign up to set email alerts
|

Neuron-glia communication via EphA4/ephrin-A3 modulates LTP through glial glutamate transport

Abstract: Astrocytes are critical participants in synapse development and function, but their role in synaptic plasticity is unclear. Eph receptors and their ephrin ligands have been suggested to regulate neuron-glia interactions and EphA4-mediated ephrin reverse signaling is required for synaptic plasticity in the hippocampus. Here we show that long-term potentiation (LTP) at the CA3-CA1 synapse is modulated by EphA4 in the postsynaptic CA1 cell and by ephrinA3, a ligand of EphA4 that is found in astrocytes. Lack of Ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
220
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(233 citation statements)
references
References 50 publications
6
220
0
2
Order By: Relevance
“…Through these mechanisms, astrocytes have been proposed to play a critical role in modulating synaptic transmission [9,10], plasticity properties [11][12][13], and longterm potentiation (LTP) [14], consistent with evidence suggesting that astrocytic Ca 2+ transients can occur in spatially restricted areas [15,16]. However, other studies have also proposed different mechanisms to account for a contribution of astrocytes to plasticity and memory [17,18]. Additionally, recent studies also suggest that astrocytes could participate, during development, in the formation of synaptic networks by regulating synaptogenesis [19] and spine pruning [20].…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…Through these mechanisms, astrocytes have been proposed to play a critical role in modulating synaptic transmission [9,10], plasticity properties [11][12][13], and longterm potentiation (LTP) [14], consistent with evidence suggesting that astrocytic Ca 2+ transients can occur in spatially restricted areas [15,16]. However, other studies have also proposed different mechanisms to account for a contribution of astrocytes to plasticity and memory [17,18]. Additionally, recent studies also suggest that astrocytes could participate, during development, in the formation of synaptic networks by regulating synaptogenesis [19] and spine pruning [20].…”
Section: Introductionmentioning
confidence: 55%
“…Previous work has suggested that adhesion molecules, by increasing transsynaptic cohesion via N-cadherin [52] or PAP-synapse sticking through EphA4/ephrin-A3 contacts [17,53], could play a role in activity-dependent synapse stability. Here, we propose that PAPs could promote structural interactions and molecular communication between synaptic partners through their reduced motility and increased coverage of the synapse.…”
Section: Discussionmentioning
confidence: 99%
“…S3A). EphA4 is involved in the regulation of synaptic plasticity (Murai et al ., 2003; Filosa et al ., 2009), and EphB2 controls both spine formation (Penzes et al ., 2003) and synaptic plasticity (Grunwald et al ., 2001, 2004; Henderson et al ., 2001; Margolis et al ., 2010). Thus, our results suggest that the age‐upregulated miRNAs downregulate the Eph/ephrin signaling pathway involved in synaptic function and plasticity.…”
Section: Resultsmentioning
confidence: 99%
“…Both dendritic spine reduction and AMPA receptor removal are critical factors that contribute to synaptic loss and dysfunction during AD progression (8,27). Another interesting feature of EphA4 is that the receptor is able to trigger reverse signaling in astrocytes via ephrin-A3 and modulate glutamate uptake by lowering glutamate transporters in glial cells (38). It is of interest to determine whether EphA4-ephrin-A3 reverse signaling is involved in synaptic dysfunctions in AD via the dysregulation of glutamate uptake, which has been reported in AD transgenic mice (39).…”
Section: Discussionmentioning
confidence: 99%